Securing Messages Using AES Algorithm and Blockchain Technology on Mobile Devices - Farissi, Al; Pradata, Arya; Miraswan, Kanda (Politeknik Ganesha Medan, 2023)
In recent years, there has been a rapid increase in the use of mobile devices and messaging applications for communication, leading to a growing concern about the security of text messages exchanged through these platforms. This study proposes a novel method that uses the AES algorithm and Blockchain to secure text messages in messaging applications on mobile devices. The AES algorithm is selected due to its faster encryption and decryption processes, which are superior to asymmetric cryptography algorithms. On the other hand, Blockchain is chosen for its inherent security properties that only allow data addition and cannot be altered. This study aims to achieve both speed and security to prevent cybercrime in text messages. The Avalanche Effect calculation and Processing Time measurement are used as the analysis methods to evaluate the proposed approach. The results show that the computation time of the message delivery process using Blockchain and AES algorithm has an average total process time of 33.59 milliseconds. Additionally, the testing results of the Avalanche Effect value show that the AES algorithm has a value of 50% for character lengths up to 16 characters and below 50% for character lengths greater than 16 characters. Based on these testing results, the proposed combination of the AES algorithm and Blockchain is an effective method for securing text messages in messaging applications. This method can offer a secure and efficient way of exchanging text messages on mobile devices and can adopt as a standard approach for messaging applications.